2011
DOI: 10.1017/s000711451100170x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in pregnant Indian women across trimesters and different seasons and its correlation with neonatal serum 25-hydroxyvitamin D levels

Abstract: The present cross-sectional study was conducted to determine the vitamin D status of pregnant Indian women and their breast-fed infants. Subjects were recruited from the Department of Obstetrics, Armed Forces Clinic and Army Hospital (Research and Referral), Delhi. A total of 541 apparently healthy women with uncomplicated, single, intra-uterine gestation reporting in any trimester were consecutively recruited. Of these 541 women, 299 (first trimester, ninety-seven; second trimester, 125; third trimester, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 55 publications
11
73
2
Order By: Relevance
“…Seventy-four percent of pregnant women had vitamin D deficiency. Marwaha et al [24] studied 541 apparently healthy women with uncomplicated, single, intrauterine gestation reporting in any trimester. Mean serum 25(OH)D of pregnant women was 23.2 (SD 12.2) nmol/l, hypovitaminosis D (25(OH)D < 50nmol/l) was observed in 96.3% of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-four percent of pregnant women had vitamin D deficiency. Marwaha et al [24] studied 541 apparently healthy women with uncomplicated, single, intrauterine gestation reporting in any trimester. Mean serum 25(OH)D of pregnant women was 23.2 (SD 12.2) nmol/l, hypovitaminosis D (25(OH)D < 50nmol/l) was observed in 96.3% of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Marwaha et al reported that Serum 25(OH) D levels were significantly lower in winter in the second and third trimesters, while serum intact parathormone (iPTH) and alkaline phosphatase levels were significantly higher in winter in all three trimesters [25]. Similar to our study, Bodnar et In contrast, two studies found no differences in first or second trimester 25(OH) D between women at low or high risk for preeclampsia who did or did not develop the disorder later in pregnancy [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the fact that the prevalence of vitamin D deficiency is reported to be high during all three trimesters in pregnant women in India [8][9][10] and this could manifest in infants at birth and beyond. Some of the previous authors maintain that vitamin D deficiency in maternal blood correlated with that in cord blood [8].…”
Section: Citationmentioning
confidence: 99%
“…However, recent studies suggest that vitamin D deficiency is very common in apparently healthy individuals at all age groups and both genders in northern as well as southern India [5][6][7]. Limited data from northern India on vitamin D status in pregnant women in all 3 trimesters reveal unexpectedly high prevalence (74-98%) of hypovitaminosis D [8][9][10]. Zargar et al report that overall 76 (83%) of the subjects studied had vitamin D deficiency in Kashmir valley of Indian subcontinent [11].…”
Section: Introductionmentioning
confidence: 99%